(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Development of solutions to problems related to consistent acceleration of agricultural production, rational use of land fund, productivity of each irrigated hectare, and its economic efficiency is of great importance. The land intensively used in agriculture in Uzbekistan is mainly irrigated land, equal to 4.28 million hectares. These lands are truly the Golden Fund of our Republic and more than 95 percent of gross agricultural products are grown on them [Valkov V.F. 1986: 1].